Vaccines against malaria - Hill, A (2011)
There is no licenced vaccine against any human parasitic disease and Plasmodium falciparum malaria, a major cause of infectious mortality, presents a great challenge to vaccine developers. This has led to the assessment of a wide variety of approaches to malaria vaccine design and development, assisted by the availability of a safe challenge model for small-scale efficacy testing of vaccine candidates. Malaria vaccine development has been at the forefront of assessing many new vaccine technologies including novel adjuvants, vectored prime-boost regimes and the concept of community vaccination to block malaria transmission. Most current vaccine candidates target a single stage of the parasite's life cycle and vaccines against the early pre-erythrocytic stages have shown most success. A protein in adjuvant vaccine, working through antibodies against sporozoites, and viral vector vaccines targeting the intracellular liver-stage parasite with cellular immunity show partial efficacy in humans, and the anti-sporozoite vaccine is currently in phase III trials. However, a more effective malaria vaccine suitable for widespread cost-effective deployment is likely to require a multi-component vaccine targeting more than one life cycle stage. The most attractive near-term approach to develop such a product is to combine existing partially effective pre-erythrocytic vaccine candidates. © 2011 The Royal Society.